Acuerdo comercial en las exportaciones del sector camaronero - García Álava, Fausto Giovanny (2020)
The present research work is entitled TRADE AGREEMENT IN EXPORTS IN THE SHRIMP SECTOR. The problem that is tried to give a solution criterion is, given that the Ecuadorian economy is dependent on oil and traditional exports, it favors or not to sign trade agreements to encourage such exports. The context is based on the consideration of the evolution of traditional exports as an instrument that benefits from trade agreements. The methodology used is related to the descriptive statistical analysis and trend models for forecasts applied to study variables such as shrimp production and exploitation. The main contribution is that for each situation a certain trend model is applied and chosen according to its lowest level of prediction error……..